(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il contenuto delle proposte di legge c. 2976 e c. 3421 (Garnero Santanchè e Palmizio) e i profili di incostituzionalità - 2. La necessità politico-normativa di un altro approccio agli Islam. Rivitalizzazione dello strumento delle Intese e legge generale sulla libertà religiosa come antidoti alla lenta deriva del riassetto normativo della legge sui culti ammessi - 3. Allegati. The law Santanchè-Palmizio proposals about the Mosques and Imams register: a refurbishment attempt of the law n.1159 / 1929? ABSTRACT: The article examines and comments the contents of the legislative proposals c. 2976 and c. 3421 (Garnero-Santanchè and Palmizio) and their unconstitutionality profiles . At the end of this parliamentary term, this examination is also the basis for thinking about political and normative necessity of another approach to Islam and, at the same time, revitalizing the Agreements instrument and the general law of religious freedom, so that they can constitute a concrete antidote to the slow and creeping drift of the normative reorganization of the law on the admitted cults.